Semi-presidential institutional models and democratic stability: comparative analysis of Lithuania and Poland - Pugačiauskas, Vykintas (Politologija, 1999)
This article evaluates the performance of semi-presidential arrangements in two newly-democratic Central and Eastern European countries, Lithuania and Poland, and addresses the question whether stable democratic performance of the regime can be attained in circumstances that differ from those of "model" semi-presidential countries such as France. Both Lithuania and Poland experienced constitutional conflicts between presidents and prime ministers, considered as inherent features of semi-presidential models. While Poland’s Constitution more clearly defines who possesses "residual powers," constitutions of both countries have shortcomings such as preventing presidents from dissolving parliament to avoid cohabitation. In addition, neither country has experienced the formation of stable traditions which are essential to the stability of this conflict-prone regime. Presidencies in both countries have been largely dependent on the ambitions of the incumbents. Presidents are constitutionally prevented from maintaining their partisan affiliation and choose anti-party or "above-party" stances themselves. Other institutional rules (such as proportional representation in the parliamentary elections in Poland and mixed system in Lithuania) also discourage the formation of stable two-block party systems most suitable for stable semi-presidentialism. Lithuania and Poland lack the conditions that made semi-presidential models stable in Western countries. It might be attributed to the transitional nature of the political systems. However, the likelihood of democratic instability in these countries remains high in the medium term.